A patient with atrial fibrillation and diabetes: selecting the optimal anticoagulant therapy regimen - A. G. Obrezan; A. E. Filippov; A. A. Obrezan (Российский кардиологический журнал)
Atrial fibrillation (AF) is a common arrhythmia in patients with type 2 diabetes (T2D). Patients with diabetes are at higher risk of AF than those without it. There is an increased risk of dysglycemia in AF. Patients with AF and concomitant diabetes are more likely to have coronary artery disease, hypertension, heart failure, while strokes in patients with AF and diabetes are more severe. Diabetes, in turn, causes the angiopathies and cardiopathy. There is a higher risk of both thrombotic and bleeding events in patients with AF and T2D. The article discusses the mutual burden of T2D and AF, as well as the risk scores for thrombotic, thromboembolic, and bleeding events. Anticoagulant therapy takes a special place in improving the prognosis in AF patients. Numerous studies and actual clinical practice have demonstrated the effectiveness of anticoagulants in the prevention of stroke and other comorbidities.